Physico-chemical attributes of a Cambisol under pasture managed with annual burns after sugarcane vinasse application - Thadeu Rodrigues de Melo; Rogério Resende Martins Ferreira; Deisi Navroski; Clarissa Tieme Matsuda Feltran; João Tavares Filho (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Sugarcane vinasse is generated in large amounts and can be utilized to improve soil attributes, especially in areas degraded by burns. The aim of the present study was to evaluate the effects of sugarcane vinasse on physico-chemical attributes of a Cambisol managed via annual burns. Methods Soil samples were collected from an annually burned area under pasture and used in an experiment in pots to evaluate the effects of dosages of vinasse (0, 18.8, 37.5, 56.3, 75.0, 112.5, and 150.0 m3 ha−1) on water-dispersible clay, $${\text{pH}}_{{{\text{H}}_{2} {\text{O}}}}$$ pHH2O , organic matter, K+, Ca2+ + Mg2+, and K+/(Ca2+ + Mg2+). Results The results showed that vinasse application reduces water-dispersible clay, does not alter $${\text{pH}}_{{{\text{H}}_{2} {\text{O}}}}$$ pHH2O , and increases organic matter, K+, Ca2+ + Mg2+, and K+/(Ca2+ + Mg2+). The water-dispersible clay was reduced by the formation of bonds with organic matter, which overlapped the repulsive forces intensified by the increment of K+/(Ca2+ + Mg2+). The estimated vinasse dosage that provided the minimum water-dispersible clay (69 g kg−1) was 110 m3 ha−1. Conclusions Vinasse can be applied to improve the physico-chemical attributes of soils degraded by annual burns.